THE IMPORTANCE OF MARKETING IN THE DEVELOPMENT OF SMALL BUSINESS AND ENTREPRENEURSHIP AND METHODS OF ITS IMPROVEMENT (Journal of Universal Science Research, 2024)
This article describes the issues of entrepreneurship and the application of the marketing concept in the enterprises of our country.